Design Get Up System Information Inventory Goods Based Web Using the Waterfall Method at CV. Tekno Maju Jaya - Siti Nur Fatonatur Rohma; Oscar Agyemang Opoku (Politeknik Siber Cerdika Internasional, 2025)
Background: Effective inventory data management is crucial for the operational success of trading companies. At CV. Technology Proceed Jaya, the process of recording incoming and outgoing stock is currently carried out conventionally using manual bookkeeping. The play problems that arise are frequent stock data discrepancies (data redundancy), slow information retrieval processes, and the risk of losing physical archives. Objective: This study aims to design and build a Web-Based Inventory Information System to address these issues. The system development method used is Waterfall, which includes requirements analysis, system design, code implementation, and testing phases Methods: The system is built using the PHP programming language with the Laravel 10 Framework and MySQL database. System functionality testing was conducted using the Black Box Testing method. Results: The results show that the developed system successfully digitized the warehouse business processes, facilitated admins in monitoring stock movements in real-time, and generated accurate reports. Based on the test results, all system features are declared valid and feasible for use. Conclusion: In conclusion, the implementation of this system significantly reduces operational errors by 85%, accelerates reporting processes from 3 days to real-time, and enhances decision-making capabilities through data-driven insights. The study demonstrates that web-based inventory systems can effectively address manual record-keeping challenges in small and medium enterprises. Practical implications include improved warehouse efficiency, reduced stock discrepancies, and better resource allocation. This research contributes to the body of knowledge on digital transformation in inventory management, particularly for SMEs in developing countries.